Hubungan Pengetahuan Dan Perilaku Pencegahan Bullying Oleh Guru Sekolah Menengah Atas Di Kelurahan Binong - Tenussa, Natalya Desilya; Pakpahan, Gresiana Romatua; Pakpahan, Gresiani Romauli; Florensa, Maria; Kasenda, Edson (Jurnal Keperawatan Muhammadiyah, 2025)
Background: Bullying is an act of violence that often occurs in the school environment however, many Middle_High School teachers do not fully know what preventive measures can be taken. Data from the Indonesian_Children_Protecting_Commission_(KPAI) noted that from 2011 to 2019 the incidence of bullying in children and adolescents reached a significant number, namely reaching 2,473 reports and the trend has continued to increase to date. Purpose: to determine the relationship between knowledge and behavior of bullying prevention by Middle_High_School teachers in Binong Village. Methods: The research design uses a correlational quantitative method using a cross sectional approach. Selection of samples by means of total sampling, obtained as many as 69 respondents. The data analysis used was univariate and bivariate frequency distribution analysis with Gamma correlation test. Results: The results of the univariate analysis showed that the majority of teachers with good knowledge (78.26%) and good behavior (94.2%). The results of the bivariate analysis showed that there was no relationship between knowledge and bullying prevention behavior by teachers in senior high schools in Binong Village with p = 0.089 (p > 0.05) and r = 0.869. Recomendation: for future researchers this research can be continued by looking at other variables that are thought to influence teacher knowledge and behavior in efforts to prevent bullying by using a more specific questionnaire to measure behavior.